Consumer Behavior and Digital Marketing Environment of an Ayurvedic Functional Foods Startup: A Case Study on Planrbro Life Sciences - Sharma, Ravin (Global journal of Business and Integral Security, 2025)
Digital marketing is a silver bullet for e-commerce-based businesses; it continuously helps both consumers and brands to understand each other’s requirements at minimal costs. In this study, we present a roadmap for start-ups in the nutraceutical domain to master their social media campaigns by closely interacting with their consumers digitally. We present a case study of PlantBro Life Sciences Private Limited, India, to get insights into the social media and E-commerce strategies on platforms like Facebook, Instagram, YouTube, Amazon and Flipkart. Next, We surveyed a housing society with 150 participants selected based on age, availability and convenience to understand the current and future scenario of Fungi-based nutraceuticals in the Indian market. Lastly, we Interviewed the Chief Executive Officers (CEOs) of four major nutraceutical brands to elucidate the efficiency of social media and e-commerce strategies on the ground level. While comparing the digital marketing strategies of PlantBro Life Sciences on both Instagram and Facebook, we recorded organic farm videos and product benefit videos posted by the founder to be the most successful ones for gaining followers and sales. Facebook did not prove to be as successful as Instagram in terms of sales because of multiple factors, such as the audience’s interests and the declining trend of the platform. The Conversion rate recorded on Instagram was 20%, while on Facebook, it was recorded to be 10%. As per the qualitative comparison of different strategies on Facebook & Instagram, influencer videos and videos featuring Bollywood stars worked the best for heavily funded brands. Brand-specific posts like organic farm videos and client testimonies worked effectively for brands with little or no external funding, like PlantBro Life Sciences. Product positioning and competitor targeting worked well for PlantBro Life Sciences, and first-page banners and video ads aced the list for brands with funding on e-commerce platforms like Amazon and Flipkart. The survey suggested people from the age group 15-30 years to be highly interested in nutraceuticals and had maximum relative insight into fungal supplements, whilst age groups 60 and above showed little interest towards them. The CEOs clearly stated that the digital marketing scenario is capital-driven and to make a mark in short time required gigantic capital for influencing the audiences.